DAKWAH DAN PERUBAHAN SOSIAL MASYARAKAT DI KOTA PALU - Muhammad Alim Ihsan (ISTIQRA, 2017)
This study aims to find out the description of Da'wa and Social Change of Society in Palu City. This research is descriptive research using qualitative approach. Informants in this study are religious leaders, community leaders, youth leaders, community, and members of the Ta'lim assembly. Data were collected using interview guidelines, and analyzed using qualitative descriptive analysis. The results of the analysis show that: (1) the social changes that occur in the community in Palu city in the long term consisting of: (a) relationship pattern, (b) settlement pattern, (c) lifestyle, and (d) 2) The role of da'wah in facing the social change of the people in Palu City are: (a) as motivator, (b) guidance, (c) relationship building, (d) organizing communication, (e) human resources, and (f) protection, and (3) Constraints da'wah in facing social change of society in Palu City can be seen from internal and external factor. internal factors are: (a) the problem of missionary officers, (b) da'wah material, (c) da'wah approach, (d) media, facilities and da'wah fund, and (e) management and system of dakwa. External factors are: (a) the progress of science and technology, (b) attack of thought (ghazwul fikri0, (c) apostasy movement, (d) foreign cultural imprealism, and (e) permissive life